2001
DOI: 10.1128/aac.45.3.878-882.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Analysis of AST-1, a Class A β-Lactamase from Nocardia asteroides Sensu Stricto

Abstract: A ␤-lactamase gene was cloned from a Nocardia asteroides sensu stricto clinical isolate. A recombinant plasmid, pAST-1, expressed the ␤-lactamase AST-1 in Escherichia coli JM109. Its pI was 4.8, and its relative molecular mass was 31 kDa. E. coli JM109(pAST-1) was resistant to penicillins and narrow-spectrum cephalosporins. The ␤-lactamase AST-1 had a restricted hydrolytic activity spectrum. Its activity was partially inhibited by clavulanic acid but not by sulbactam and tazobactam. AST-1 is an Ambler class A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
(32 reference statements)
2
18
0
Order By: Relevance
“…1). BOR-1 shared 42 to 45% amino acid identity with the most closely related enzymes, the naturally occurring ␤-lactamases L-2 from S. maltophilia, PenA from Burkholderia cepacia, FAR-1 from Nocardia farcinica, AST-1 from Nocardia asteroides, YENT from Yersinia enterocolitica, and SHV-1 from Klebsiella pneumoniae, and the plasmid-mediated ␤-lactamase TEM-1 (3,6,7). The surrounding sequences of the bla BOR-1 gene in B. bronchiseptica and B. parapertussis were identical.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1). BOR-1 shared 42 to 45% amino acid identity with the most closely related enzymes, the naturally occurring ␤-lactamases L-2 from S. maltophilia, PenA from Burkholderia cepacia, FAR-1 from Nocardia farcinica, AST-1 from Nocardia asteroides, YENT from Yersinia enterocolitica, and SHV-1 from Klebsiella pneumoniae, and the plasmid-mediated ␤-lactamase TEM-1 (3,6,7). The surrounding sequences of the bla BOR-1 gene in B. bronchiseptica and B. parapertussis were identical.…”
mentioning
confidence: 99%
“…Selection of recombinant clones was performed on Mueller-Hinton (MH) plates containing 50 g of amoxicillin and 30 g of kanamycin per ml. Once cloned, the PCR product was sequenced on both strands as described previously (6), and the ␤-lactamase gene sequence revealed identity with that found in the databases for B. bronchiseptica RB50. Disk diffusion susceptibility testing performed for E. coli DH10B (pFL-1) suggested that the cloned gene encoded a functional ␤-lactamase named BOR-1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cefoxitin, dicloxacillin, imipenem, and aztreonam are poorly recognized by the enzyme, and the protein is inhibited by the penem inhibitor BRL42715 and, to a lesser extent, clavulanic acid. The specificity profile is similar overall to those of CTX-M-type enzymes; some TEM-derived extended-spectrum ␤-lactamases (ESBLs); the chromosomally encoded ESBLs from Citrobacter sedlakii and Yersinia enterocolitica; and ␤-lactamases identified in the genera Nocardia, Kluyvera, and Burkholderia (1,12,31,33,35,37). At the aminoacid level, the mature protein shares 70% identity with the ␤-lactamase of Mycobacterium smegmatis and between 40 and 45% with the aforementioned proteins.…”
mentioning
confidence: 75%